2008
DOI: 10.1080/09593980802278959
|View full text |Cite
|
Sign up to set email alerts
|

Interrater reliability of the Modified Modified Ashworth Scale (MMAS) for patients with wrist flexor muscle spasticity

Abstract: The measurement of spasticity is part of the neurological examination of patients with disorders of the central nervous system. Recently, the Modified Modified Ashworth Scale (MMAS) was developed for the characterization of muscle spasticity. The purpose of this study was to determine the interrater reliability of the MMAS in the assessment of wrist flexor muscle spasticity in adult patients after upper motoneuron lesions resulted in hemiplegia. Thirty hemiplegic patients (17 males and 13 females) with a mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 41 publications
2
56
1
3
Order By: Relevance
“…So far, the findings on the reliability of the MMAS have been good and very good [17][18][19][20][21]. In this study, moderate reliability was observed for the hip adductors and good reliability for knee extensors; however, these are lower than previous measures of intrarater reliability [17].…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…So far, the findings on the reliability of the MMAS have been good and very good [17][18][19][20][21]. In this study, moderate reliability was observed for the hip adductors and good reliability for knee extensors; however, these are lower than previous measures of intrarater reliability [17].…”
Section: Discussioncontrasting
confidence: 50%
“…The relationship between the MMAS scores obtained from the wrist flexor muscle group and the H Slope /M Slope and H Max /M Max ratios was statistically significant (r = 0.39, p = 0.04) [22].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Sua importância mostra-se relevante para conhecer a eficácia das intervenções terapêuticas ou orientar as decisões de tratamento (NAGHDI et al, 2008).…”
Section: Espasticidade E Alteração De Forçaunclassified
“…A espasticidade é um problema de longo prazo e, para o desenvolvimento de programas de reabilitação efetivos, é fundamental a realização de ensaios rigorosos onde os instrumentos utilizados têm se mostrado imprescindíveis para orientar as decisões de tratamento e para medir o progresso em pacientes com espasticidade (NAGHDI et al, 2008).…”
Section: Escalasunclassified